Mutations in the Basic Region of the Mason-Pfizer Monkey Virus Nucleocapsid Protein Affect Reverse Transcription, Genomic RNA Packaging, and the Virus Assembly Site - Dostálková, Alžběta; Kaufman, Filip; Křížová, Ivana; Kultová, Anna; Strohalmová, Karolína; Hadravová, Romana; Ruml, Tomáš; Rumlová, Michaela (Journal of virology, 2018)
In addition to specific RNA-binding zinc finger domains, the retroviral Gag polyprotein contains clusters of basic amino acid residues that are thought to support Gag-viral genomic RNA (gRNA) interactions. One of these clusters is the basic K16NK18EK20 region, located upstream of the first zinc finger of the Mason-Pfizer monkey virus (M-PMV) nucleocapsid (NC) protein. To investigate the role of this basic region in the M-PMV life cycle, we used a combination of in vivo and in vitro methods to study a series of mutants in which the overall charge of this region was more positive (RNRER), more negative (AEAEA), or neutral (AAAAA). The mutations markedly affected gRNA incorporation and the onset of reverse transcription. The introduction of a more negative charge (AEAEA) significantly reduced the incorporation of M-PMV gRNA into nascent particles. Moreover, the assembly of immature particles of the AEAEA Gag mutant was relocated from the perinuclear region to the plasma membrane. In contrast, an enhancement of the basicity of this region of M-PMV NC (RNRER) caused a substantially more efficient incorporation of gRNA, subsequently resulting in an increase in M-PMV RNRER infectivity. Nevertheless, despite the larger amount of gRNA packaged by the RNRER mutant, the onset of reverse transcription was delayed in comparison to that of the wild type. Our data clearly show the requirement for certain positively charged amino acid residues upstream of the first zinc finger for proper gRNA incorporation, assembly of immature particles, and proceeding of reverse transcription.IMPORTANCE We identified a short sequence within the Gag polyprotein that, together with the zinc finger domains and the previously identified RKK motif, contributes to the packaging of genomic RNA (gRNA) of Mason-Pfizer monkey virus (M-PMV). Importantly, in addition to gRNA incorporation, this basic region (KNKEK) at the N terminus of the nucleocapsid protein is crucial for the onset of reverse transcription. Mutations that change the positive charge of the region to a negative one significantly reduced specific gRNA packaging. The assembly of immature particles of this mutant was reoriented from the perinuclear region to the plasma membrane. On the contrary, an enhancement of the basic character of this region increased both the efficiency of gRNA packaging and the infectivity of the virus. However, the onset of reverse transcription was delayed even in this mutant. In summary, the basic region in M-PMV Gag plays a key role in the packaging of genomic RNA and, consequently, in assembly and reverse transcription.
Keywords: mutace; buněčné linie; Gene Products, gag; HEK293 Cells; reverzní transkripce; sekvence aminokyselin; zinkové prsty; RNA, Viral; nukleokapsida - proteiny; lidé; Zinc Fingers; genové produkty gag; Mutation; Amino Acid Sequence; HEK293 buňky; Cell Line; RNA virová; Virus Assembly; sestavení viru; Mason-Pfizer monkey virus; Masonův-Pfizerův opičí virus; Nucleocapsid Proteins; Reverse Transcription; Humans